The Clostridium difficile cell wall protein CwpV is antigenically variable between strains, but exhibits conserved aggregation-promoting function. - Catherine B Reynolds; Jenny E Emerson; Lucia de la Riva; Robert P Fagan; Neil F Fairweather (PLoS Pathogens)
Clostridium difficile is the main cause of antibiotic-associated diarrhea, leading to significant morbidity and mortality and putting considerable economic pressure on healthcare systems. Current knowledge of the molecular basis of pathogenesis is limited primarily to the activities and regulation of two major toxins. In contrast, little is known of mechanisms used in colonization of the enteric system. C. difficile expresses a proteinaceous array on its cell surface known as the S-layer, consisting primarily of the major S-layer protein SlpA and a family of SlpA homologues, the cell wall protein (CWP) family. CwpV is the largest member of this family and is expressed in a phase variable manner. Here we show CwpV promotes C. difficile aggregation, mediated by the C-terminal repetitive domain. This domain varies markedly between strains; five distinct repeat types were identified and were shown to be antigenically distinct. Other aspects of CwpV are, however, conserved. All CwpV types are expressed in a phase variable manner. Using targeted gene knock-out, we show that a single site-specific recombinase RecV is required for CwpV phase variation. CwpV is post-translationally cleaved at a conserved site leading to formation of a complex of cleavage products. The highly conserved N-terminus anchors the CwpV complex to the cell surface. Therefore CwpV function, regulation and processing are highly conserved across C. difficile strains, whilst the functional domain exists in at least five antigenically distinct forms. This hints at a complex evolutionary history for CwpV.